Personality Factors and Depressive Configurations. An Exploratory Study in an Italian Clinical Sample - Straccamore, Francesca; Ruggi, Simona; Lingiardi, Vittorio; Zanardi, Raffaella; Vecchi, Sara; Oasi, Osmano (Frontiers in Psychology, 2017)
Introduction. This study focuses on the relationship between personality configurations and depressive experiences. More specifically, the aim of this study is to investigate the relationship between self-criticism and dependency and personality styles or disorders, exploring the association between personality features and depressive symptoms. The two-configurations model of personality developed by Sidney Blatt (2004, 2008) is adopted as a reference point in sharing a valid framework and in understanding the results. Methods. Five instruments are administered to 51 participants with a diagnosis of depressive disorder, in accordance with DSM-IV-TR (APA, 2000): self-criticism and dependency dimensions of depression are measured with the Depressive Experiences Questionnaire (DEQ); self-reported depression is assessed with the Beck Depression Inventory-II (BDI-II); observer-rated depression is assessed with the Hamilton Depression Rating Scale (HDRS); personality is assessed with the Clinical Diagnostic Interview (CDI) and the Shedler Westen Assessment Procedure-200 (SWAP-200). Results. Only self-criticism, and not dependency, is associated with depressive symptoms. In addition, the SWAP Borderline PD Scale and the Dysphoric: emotionally dysregulated Q-factor emerge as significant in predicting depression. Conclusions. Findings support the assumption that depressive personality configurations can enhance the vulnerability to developing depression. Theoretical and clinical implications of these results are discussed.